Impact of screen time on sleep quality among undergraduate medical students in Patna, Bihar: a cross-sectional study - Gupta, Animesh; Anubhav; Priyadarshi, Apoorva; Kaur, Navneet; Priya, Tanu; Singh, Nandini (International Journal of Research in Medical Sciences, 2025)
Background: Digital screens have become omnipresent in the lives of young adults, especially medical students, raising concerns about the influence of extended screen exposure on sleep quality. Growing evidence suggests screen time, particularly near bedtime, adversely affects sleep parameters, potentially diminishing cognitive and academic performance. The objective of this study was to assess the association between total screen time and sleep quality among undergraduate medical students in Patna, Bihar, India. Methods: A cross-sectional study was conducted in June 2025 among 510 undergraduate medical students from seven medical colleges in Patna. Data was collected using a pre-tested, semi-structured Google Forms questionnaire, which included socio-demographic details, screen use patterns, and the Pittsburgh sleep quality index (PSQI) for sleep assessment. Descriptive and inferential statistics were analyzed with statistical package for the social sciences (SPSS) trial version 25. Results: The mean participant age was 22.4 years; 59.9% were male. Most students reported 2–4 hours (44.9%) followed by 5–8 hours (29.6%) of screen time per day. Only 16.3% reported sleeping more than 7 hours per night. Use of screens within 1 hour before sleep was reported by 46.7% of participants. PSQI scores showed that 68.2% of students experienced poor sleep quality (global PSQI >5). Extended and late-night screen time was significantly associated with higher PSQI scores, indicating poorer sleep. Conclusion: High levels of screen exposure, especially at night, are associated with significantly reduced sleep quality among medical students. Responsible digital hygiene and structured interventions are crucial to prevent sleep disturbances in this vulnerable population.